Exploring The Implementation of Technological Pedagogical and Content Knowledge (TPACK) in Teaching English at Senior High School - Eva Fitriani Syarifah; afief fakhruddin; Lestari, Fidya Rahayu Apriyani (Papanda Journal of English Education, 2023)
TPACK means teacher’s ability to facilitate students. A good learning process needs complex understanding that correlates three knowledge resources; technology, pedagogy and content. From TPACK, we know that teachers knowledge about how to facilitate students learning from certain content by pedagogy and technology approach. This research aims to explain the implementation of TPACK in teaching English at senior high school and to explain the obstacle experienced by English teacher in implementing TPACK in teaching English at senior high school. This research was conducted in one of the senior high school. This research used a case study with a qualitative method. Sample in this research is one English teacher. The process collecting data is done through observation, interview and questionnaire. The research results show the implementation of TPACK in teaching English in senior high school can be categorized as good in implemented TPACK based on sixth component, Technological Knowledge, Pedagogical Knowledge, Content Knowledge, Technogical Pedagogical Knowledge, Technological Content Knowledge, Pedagogical Content Knowledge and Technological Pedagogical and Content Knowledge of TPACK. The obstacle faced by the English teacher in implementing TPACK in learning process, teacher was poor in one component Technological Knowledge such as lack of IT literacy. Based on the research, researcher it can be conclude that in implementation of TPACK in teaching English it was found that there were still several part of TPACK component that had not been implemented properly in classroom learning.The researcher suggested that this research can be a guideline for other researchers in conducting research on TPACK. Other researchers can also explore teachers obstacle in teaching English based on the TPACK framework.